Effective p-cresol removal through catalytic liquid-phase oxidation under moderate conditions using Pt/CeO2-ZrO2-SnO2/SBA-16 as a catalyst - Abdul Rohman Supandi (Journal of Asian Ceramic Societies, 2020)
Cresol is among the phenolic compounds that are frequently found in industrial wastewater streams. Most notably, p-cresol has the highest toxicity and the highest permeability effect on skin of all the cresol isomers; hence, wastewater treatment for p-cresol removal is an important issue. This study was aimed at determining a method of removing p-cresol effectively under moderate conditions by catalytic oxidation. To this end, we synthesized a Pt/CeO2-ZrO2-SnO2/SBA-16 catalyst by supporting Pt as the activator and CeO2-ZrO2-SnO2 as the promoter on an SBA-16 support. As concerns the promoter, the introduction of ZrO2 and SnO2 improved its redox properties, and the superior redox properties of Ce0.68Zr0.17Sn0.15O2 facilitated generation of oxidized platinum ions (Pt2+) with a high phenolic compound oxidation capability compared to metallic platinum (Pt0). Among the catalysts prepared, Pt/CeO2-ZrO2-SnO2/SBA-16 with high Pt2+ content exhibited the highest catalytic activity for p-cresol oxidation, and p-cresol was completely removed under moderate reaction conditions of 80°C for 4 h under atmospheric pressure.